STUDENTS' CREATIVE THINKING PROCESS IN SOLVING MATHEMATICS PROBLEMS ASSISTED BY CHATGPT REVIEWED FROM SELF-EFFICACY - Astin Anas; Masriyah; Abdul Haris Rosyidi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Creative thinking is an essential component of mathematical problem solving, yet its development remains underexplored, particularly regarding how students with different self-efficacy levels engage in creative thinking processes during ChatGPT-assisted mathematical problem solving. This study aimed to describe the creative thinking processes of students with high, moderate, and low self-efficacys in solving mathematical problems assisted by ChatGPT. A descriptive qualitative approach was employed, involving three Grade XI students selected through purposive sampling to represent high, moderate, and low self-efficacys categories with equivalent mathematical abilities. Data were collected through self-efficacy questionnaires, mathematical problem-solving tasks, interviews, and then analyzed using interactive qualitative analysis with time triangulation. The results showed that students across all self-efficacy levels completed the stages of preparation, mini-incubation, illumination, and verification. However, differences emerged in their levels of independence, idea development, and depth of verification; student with high self-efficacy demonstrated more independent and reflective thinking processes than those with moderate and low self-efficacy. These findings indicate that self-efficacy influences the quality of students’ creative thinking processes when utilizing ChatGPT for mathematical problem solving.